Cost analysis of implementing a telegeriatrics ecosystem with nursing homes: panel data analysis. Issue 4 (1st October 2020) - Low, James Alvin; Hui Jin, Toh; Tan Lean Chin, Laurence; Agarwal, Neha; Kim Huat, Goh; Yeow, Adrian; Soh, Christina
ABSTRACT: Our study analyzed the economicimpact of a telegeriatrics programme on care of nursing homeresidents, from the healthcare system provider's perspective. Thisis a retrospective, archival data analysis of multiple data sourcesin 4 nursing homes of Singapore from 2010 to 2015. Individualsadmitted to nursing homes and have undergone telemedicineconsultations (N=859) from 2010 to 2015 were recruited. Weconducted a cost analysis of the programme by reviewing pasthospital admissions' and specialist outpatient clinic (SOC) visits'billing records, nurse training records, and key performanceindicators' reports. A significant relationship was observed betweenteleconsultations and SOC visit cost ( β1 = -83.366, p-value<0.01) and between teleconsultations and inpatient cost ( β1 =-470.971, p-value <0.05). Remote video consultations could reduceunnecessary SOC visits and hospital admissions, and thereforelead to cost savings. Training of nursing home nurses couldtranslate to cost savings as a result of decreased ED transfers.